La prise en compte du développement local dans le code des investissements en Algérie - ZOUITEN, Abderrezak (Journal of Human Sciences, 2015)
Areas requiring a special State contribution or areas to develop, within the meaning of article 10 of order No. 01 - 03 relating to the development of investment, are lifeless spaces which the State has decided to encourage the establishment of units of production of goods or services to introduce economic, social, cultural and environmental progress with aim local development. Economic investment being carrier of all these vectors, it is designed as a factor able to redress regional disparities